Covid-19 Hoax Detection Using KNN in Jaccard Space - Ema Utami; Ahmad Fikri Iskandar; Wahyu Hidayat; Agung Budi Prasetyo; Anggit Dwi Hartanto (IndoCEISS in colaboration with Universitas Gadjah Mada, Indonesia., 2021)
Social media has become a communication key to spark thinking, dialogue and action around social issues. Hoax is information that added or subtracted from the content of the actual news. The spread of unconfirmed Covid-19 news can cause public concern. The purpose of this research was to modify KNN with Jaccard Space in the classification of hoax news related to Covid-19. The data used from Jabar Saber Hoaks and Jala Hoaks. The classification results with KNN with Jaccard Space and stemming Nazief & Adriani get the highest accuracy than other models in this research. The accuracy of the KNN model on the Jaccard Space with stemming Nazief & Adriani and K = 5 was 75.89%, while for Naïve Bayes was 65.18%.